Caribbean immigration to the US 1965-1989. - CARLSON, Alvar W. (1994)
Notes that the Caribbean is today the source of about one-third of America's immigrants from the Western Hemisphere and nearly 15 percent of its worldwide immigrants. Presents data tabulating the major sources of immigrants.